1996
DOI: 10.1111/j.1432-1033.1996.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulatory Tyrosine of Xenopus Mitogen‐Activated Protein Kinase is out of the Reach of the Enzyme Catalytic Center After Autophosphorylation

Abstract: Autophosphorylation of the recombinant mitogen-activated protein kinase (MAPK) from Xenopus Zaevis has been studied to detect the conformational changes in the region of regulatory phosphorylation upon enzyme activation. Slow autophosphorylation of Xenopus MAPK occured predominantly on tyrosine, the major phosphoregulatory site of MAPKs, through an intramolecular mechanism and was accompanied by a low magnitude stimulation of the catalytic activity towards an exogenous substrate, myelin basic protein. Autophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Bradshaw et al showed that interaction of the cytoplasmic tail of CD152, a mediator of T cell activation, with a clathrin‐associated protein is negatively regulated by tyrosine phosphorylation [25]. Various other studies employing epitope‐specific antibodies, protein binding assays and structural methods have provided evidence for a determinant influence of tyrosine phosphorylation on protein conformation [26–31].…”
Section: Resultsmentioning
confidence: 99%
“…Bradshaw et al showed that interaction of the cytoplasmic tail of CD152, a mediator of T cell activation, with a clathrin‐associated protein is negatively regulated by tyrosine phosphorylation [25]. Various other studies employing epitope‐specific antibodies, protein binding assays and structural methods have provided evidence for a determinant influence of tyrosine phosphorylation on protein conformation [26–31].…”
Section: Resultsmentioning
confidence: 99%
“…1996), a Src family kinase, or GST‐MAPK. GST‐MAPK was purified from bacteria as described previously (Tokmakov et al . 1996).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro phosphorylation assay of the immunoprecipitated xhnRNP K (see above) was also carried out with the use of the purified bovine brain c-Src or Fyn , a Src family kinase, or GST-MAPK. GST-MAPK was purified from bacteria as described previously (Tokmakov et al 1996). Phosphorylation reaction proceeded for 20 min at 30°C and was stopped by the addition of EDTA (for immunoprecipitation and immunoblotting) or Laemmli's SDS sample buffer (for immunoblotting).…”
Section: In Vitro Phosphorylation Assays In Cell-free Extractsmentioning
confidence: 99%